Synthesis, structural elucidation and biological activities of some novel sulfonyl hydrazones as antibacterial agents - ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (MARMARA UNIV, 2021)
In this study, some N'-(substituted arylmethylidene)-4-nitrobenzenesulfonohydrazide derivatives were synthesis by reading various aldehydes and 4-nitrobenzenesulfonohydrazide. The structural characterization of the compounds was performed by IR, H-1-NNIR and TOF-MS (compounds 3b and 3e) spectroscopic data besides elementel analyses results. The antibacterial activities of these compounds were examined against some bacteria species. The compounds showed the highest activity against Pseudomonas aeruginosa ATCC 27853. Also, anti-quorum sensing activities have been determined using a biosensor bioassay with Chromobacterium violaceum CV026 and the signaling molecule N-hexanoyl-L-homoserine lactone. All the compounds were subjected for ADME predictions by computational method.
Keywords: Sulfonyl hydrazone; hydrazide; MIC; antibacterial activity; quorum sensing; INHIBITION